Penerapan Model Pembelajaran Problem Based Learning untuk Meningkatkan Kemampuan Berpikir Kritis dan Hasil Belajar Matematika Siswa Kelas IV Sekolah Dasar - Sakrani, Sakrani (Universitas Sebelas Maret, 2020)
The purpose of this study is to describe the application of PBL to improve critical thinking skills and learning outcomes, to determine the improvement of students' critical thinking skills, and to determine the improvement of student learning outcomes. This type of research is Classroom Action Research (CAR) with two cycles. The subjects of this study were 4th grade students of SD Negeri 14 Padang Aro which opened 16 students. Data collection techniques using tests and non-tests. This research instrument uses story questions, interviews, questionnaire sheets and observations. Analysis of the data used is descriptive quantitative analysis. The results showed that the use of the Problem Based Learning learning model could improve critical thinking skills and learning outcomes in solving stories in mathematics in grade 4 SD Negeri 14 Padang Aro. This can be proven from the ability to critically assess students from the initial condition (pre-cycle) which is 60.32 (no) to 73.21 (critical enough) at the end of the second cycle. An increase also occurred in student learning outcomes from the average value of learning outcomes in the initial conditions of 62.86, increasing in the first cycle to 69 and in the second cycle to 80. The percentage of students who achieved the KKM increased from the initial condition 45.84%, increased to 70.83% in the first cycle evaluation and to 91.67% in the second cycle evaluation.